ANALISIS KINERJA OPERASIONAL ANGKUTAN UMUM MIKROLET DI KOTA PALANGKA RAYA - Desi Riani (Lambung Mangkurat University Press, 2012)
Nowadays, the growth of the city and population of Palangka Raya as capital city and the center of governance of Central Kalimantan is fast enough, so it results a certain planology pattern and dependention of the edge part which expanding to downtown and center of the business that also results the accretion of townee journey then, thus require the transportation service to serve it. Transportation service that serving during the time is ‘mikrolet’ (microlight car). However, the ‘mikrolet’ in Palangka Raya city recently less enthused by society. It is influenced by performance level of ‘mikrolet’ which has been less maximal. Through the study based on Standard of World Bank and Letter of Decision of Director General of Land Transportation No. 687/DRJD/2002 and Pacific Consultan International (PCI) Method, a performance parameter that became the base in determining how the operational performance of city transport and then the amount of ideal vehicles to influence the scheduling of operational of the city transportation so that operators would get the earnings relatively equal could be analysed. The parameters of operational performance of public transportation ‘mikrolet’ were service frequency, passenger amount, vehicle speed, travel time, cycle time, headway, load factor and operating cost, however the most influencing parameters were vehicle speed, travel time, cycle time, and headway. The optimum number of vehicle requirement for each line was determined by regulated cycle time value divided by regular headway, so that 15 vehicles in line A obtained, 10 vehicles in line B obtained, 11 vehicles in line C obtained, 8 vehicles in line D obtained, 17 vehicles in line E obtained, and 14 vehicles in line F obtained. After a scheduling based on regular headway and regulated time travel and vehicle speed, the performances of operational and service of the public transport ‘mikrolet’ became more regular compared to non-scheduled.